Unifying Virulence Evaluation in Toxoplasma gondii: A Timely Task - Calero-Bernal, Rafael; Fernández-Escobar, Mercedes; Katzer, Frank; Su, Chunlei; Ortega-Mora, Luis Miguel (Frontiers in Cellular and Infection Microbiology, 2022)
Toxoplasma gondii, a major zoonotic pathogen, possess a significant genetic and phenotypic diversity that have been proposed to be responsible for the variation in clinical outcomes, mainly related to reproductive failure and ocular and neurological signs. Different T. gondii haplogroups showed strong phenotypic differences in laboratory mouse infections, which provide a suitable model for mimicking acute and chronic infections. In addition, it has been observed that degrees of virulence might be related to the physiological status of the host and its genetic background. Currently, mortality rate (lethality) in outbred laboratory mice is the most significant phenotypic marker, which has been well defined for the three archetypal clonal types (I, II and III) of T. gondii; nevertheless, such a trait seems to be insufficient to discriminate between different degrees of virulence of field isolates. Many other non-lethal parameters, observed both in in vivo and in vitro experimental models, have been suggested as highly informative, yielding promising discriminatory power. Although intra-genotype variations have been observed in phenotypic characteristics, there is no clear picture of the phenotypes circulating worldwide; therefore, a global overview of T. gondii strain mortality in mice is presented here. Molecular characterization has been normalized to some extent, but this is not the case for the phenotypic characterization and definition of virulence. The present paper proposes a baseline (minimum required information) for the phenotypic characterization of T. gondii virulence and intends to highlight the needs for consistent methods when a panel of T. gondii isolates is evaluated for virulence.